Promoting cognitive skill among engineering undergraduates with technological software - Khuzairi N.M.B.S.; Sidhu M.S. (IGI Global, 2023)
This chapter reviews the infusion of technology tools such as the integration of computers into programs like simulation to promote higher cognitive skills among engineering undergraduates. With the constant change of technology and education, it is necessary to refine the current teaching and learning process to not only promote understanding but also to create room for engineering undergraduates to process the information with higher-order cognitive skills. The authors examine the evolution of engineering education against the backdrop of the problems faced in the learning environments and the technological trends in engineering curriculum. To this end, the authors propose strategies to promote higher-order cognitive skills among engineering undergraduates based on the evolution of technology in engineering as well as the challenges faced in the implementation of such tools in teaching and learning. © 2015, IGI Global.